Alcohol use during a trial of N-acetylcysteine for adolescent marijuana cessation. (December 2016) - Squeglia, Lindsay M.; Baker, Nathaniel L.; McClure, Erin A.; Tomko, Rachel L.; Adisetiyo, Vitria; Gray, Kevin M.
Abstract: Aims: Current adolescent alcohol treatments have modest effects and high relapse rates. Evaluation of novel pharmacotherapy treatment is warranted. N -acetylcysteine (NAC), an over-the-counter antioxidant supplement with glutamatergic properties, is a promising treatment for marijuana cessation in adolescents; however, its effects on adolescent drinking have not been examined. To that end, this secondary analysis evaluated: (1) the effect of NAC vs. placebo on alcohol use over an eight-week adolescent marijuana cessation trial and (2) the role of marijuana cessation and reduction on subsequent alcohol use. Methods: Marijuana-dependent adolescents (ages 15–21; N = 116) interested in treatment were randomized to NAC 1200 mg or matched placebo twice daily for eight weeks. Participants were not required to be alcohol users or interested in alcohol cessation to qualify. Results: There were no demographic or baseline alcohol use differences between participants randomized to NAC vs. placebo ( p s > 0.05). Of the 89 participants returning for ≥ one visit following randomization, 77 reported ≥ one alcoholic drink in the 30 days prior to study entry and averaged 1.3 (SD = 1.4) binge drinking days per week. During treatment, less marijuana use (measured via urine cannabinoid levels) was associated with less alcohol use in the NAC-treated group but not in the placebo-treated group ( p = 0.016). Conclusions: There was no evidence of compensatory alcohol use during marijuana treatment. In fact, in the NAC group, lower levels of marijuana use were associated with less alcohol use, suggesting NAC effects may generalize to other substances and could be useful in decreasing adolescent alcohol use. NAC trials specifically focused on alcohol-using adolescents are warranted. Highlights: N -acetylcysteine (NAC) is a promising target medication for treating addiction. In the NAC-treated group, less marijuana use was associated with less alcohol use. This relationship was not found in the placebo group. More research is warranted to understand the effect of NAC on adolescent alcohol use.